A shadow rate model with time-varying lower bound of interest rates - Tomi Kortela (Bank of Finland, 2016)
Typically a constant – or zero – lower bound for interest rates is applied in shadow rate term structure models. However, euro area yield curve data suggest that a time-varying lower bound might be appropriate for the euro area. I show that this indeed is the case, i.e. a shadow rate model with time-varying lower bound outperforms the constant lower bound model in euro area data. I argue that the time-variation in the lower bound is related to the deposit facility rate and, thus, to monetary policy. This time-variation in the lower bound gives a new channel via which monetary policy may affect the yield curve in a shadow rate model. I show that the intensity of this channel depends on how tightly the lower bound restricts the yield curve, and I argue that this channel has recently become important for the euro area.
URN:NBN:fi:bof-201606271357
Keywords: E43; E44; E52; 330